2002
DOI: 10.1034/j.1398-9995.57.s72.22.x
|View full text |Cite
|
Sign up to set email alerts
|

A genetic analysis of lupus

Abstract: Systemic lupus erythematosus (SLE) is a complex multigenic inherited disease with susceptibility determined by a combination of genetic, environmental and stochastic factors. Although not yet defined, recent technical advances have provided the means to dissect the component genetic contributions of polygenic traits. We have applied such approaches to mouse models of spontaneous SLE and, in this report, summarize our genome wide mapping studies that identified loci predisposing to several major lupus-related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…Phenotypic components of the model, such as mortality, glomerulonephritis and anti-chromatin antibody production, may be differentially influenced by a variety of genes. For example, Lbw8 has been linked to anti-chromatin antibody expression, whereas Lbw6 has been linked to mortality and glomerulonephritis [65]. We examined both autoantibody production and target organ damage, and our microarray analysis suggested that the main effect of coumestrol was on immune response rather than target organ susceptibility.…”
Section: Discussionmentioning
confidence: 97%
“…Phenotypic components of the model, such as mortality, glomerulonephritis and anti-chromatin antibody production, may be differentially influenced by a variety of genes. For example, Lbw8 has been linked to anti-chromatin antibody expression, whereas Lbw6 has been linked to mortality and glomerulonephritis [65]. We examined both autoantibody production and target organ damage, and our microarray analysis suggested that the main effect of coumestrol was on immune response rather than target organ susceptibility.…”
Section: Discussionmentioning
confidence: 97%
“…Several autoimmune loci (Lbw, Sle, Sle suppressor (Sles), Lmb and Asm2) associated with the development of generalized autoimmune disease in NZB/W, NZM2410 and (MRL-Fas lpr  B6-Fas lpr )F 2 (abbreviated as MBF2), or MRL-lpr mice, have been genetically mapped [30][31][32][33][34][35][36][37][38]. These models primarily exhibit a B-cell defect, with an accompanying T-cell defect, and the mice exhibit Total IgG2b…”
Section: Discussionmentioning
confidence: 99%
“…The point plot gives a diagrammatic explanation of the various parameters we encounter in the ADMET Analysis test. Before docking, energy of both the LIGANDS and the recept or proteins are reduced to the minimum, to make the molecules table and the docking efficient [11][12][13][14]. This is the most vital step of this research.…”
Section: Admet Of Sterolmentioning
confidence: 99%